Microwave-induced co-processing of coal and biomass - Yan, Jie-Feng (2015)
Pyrolysis is an attractive alternative for the conversion of solid fuels to valuable chemicals and bio-fuels. In order to obtain more H2 and syngas from pyrolysis of coal and biomass, microwave has been adopted to enhance the co-pyrolysis of coal and biomass, which has been investigated systematically in this study.